MTORC2 regulates multiple aspects of NKT‐cell development and function. Issue 3 (27th January 2017) - Sklarz, Tammarah; Guan, Peng; Gohil, Mercy; Cotton, Renee M.; Ge, Moyar Q.; Haczku, Angela; Das, Rupali; Jordan, Martha S.
Abstract : iNKT cells shape immune responses through cognate interactions and cytokine release. Using Rictor fl/fl CD4cre + mice we demonstrate mTORC2 is required for general iNKT‐cell expansion in response to TCR and CD28 signals and for specific development of the NKT‐17 subset. Abstract : Invariant NKT (iNKT) cells bridge innate and adaptive immunity by rapidly secreting cytokines and lysing targets following TCR recognition of lipid antigens. Based on their ability to secrete IFN‐γ, IL‐4 and IL‐17A, iNKT‐cells are classified as NKT‐1, NKT‐2, and NKT‐17 subsets, respectively. The molecular pathways regulating iNKT‐cell fate are not fully defined. Recent studies implicate Rictor, a required component of mTORC2, in the development of select iNKT‐cell subsets, however these reports are conflicting. To resolve these questions, we used Rictor fl/fl CD4cre + mice and found that Rictor is required for NKT‐17 cell development and normal iNKT‐cell cytolytic function. Conversely, Rictor is not absolutely required for IL‐4 and IFN‐γ production as peripheral iNKT‐cells make copious amounts of these cytokines. Overall iNKT‐cell numbers are dramatically reduced in the absence of Rictor. We provide data indicating Rictor regulates cell survival as well as proliferation of developing and mature iNKT‐cells. Thus, mTORC2 regulates multiple aspects of iNKT‐cell development and function.